Metformin facilitates mesenchymal stem cell-derived extracellular nanovesicles release and optimizes therapeutic efficacy in intervertebral disc degeneration. (July 2021) - Liao, Zhiwei; Li, Shuai; Lu, Saideng; Liu, Hui; Li, Gaocai; Ma, Liang; Luo, Rongjin; Ke, Wencan; Wang, Bingjin; Xiang, Qian; Song, Yu; Feng, Xiaobo; et al.
Abstract: Extracellular vesicles (EVs) are extracellular nanovesicles that deliver diverse cargoes to the cell and participate in cell communication. Mesenchymal stem cell (MSCs)-derived EVs are considered a therapeutic approach in musculoskeletal degenerative diseases, including intervertebral disc degeneration. However, limited production yield and unstable quality have impeded the clinical application of EVs. In the present study, it is indicated that metformin promotes EVs release and alters the protein profile of EVs. Metformin enhances EVs production via an autophagy-related pathway, concomitantly with the phosphorylation of synaptosome-associated protein 29. More than quantity, quality of MSCs-derived EVs is influenced by metformin treatment. Proteomics analysis reveals that metformin increases the protein content of EVs involved in cell growth. It is shown that EVs derived from metformin-treated MSCs ameliorate intervertebral disc cells senescence in vitro and in vivo . Collectively, these findings demonstrate the great promise of metformin in EVs-based intervertebral disc regeneration. Graphical abstract: Image 1